Local Land‐Use Planning to Conserve Biodiversity: Planners’ Perspectives on What Works - DAVID L. STOKES; MARIAN F. HANSON; DEBORAH D. OAKS; JAIME E. STRAUB; AILEEN V. PONIO (Conservation Biology, 2010)
Because habitat loss due to urbanization is a primary threat to biodiversity, and land‐use decisions in urbanizing areas are mainly made at the local level, land‐use planning by municipal planning departments has a potentially important—but largely unrealized—role in conserving biodiversity. To understand planners’ perspectives on the factors that facilitate and impede biodiversity conservation in local planning, we interviewed directors of 17 municipal planning departments in the greater Seattle (Washington, U.S.A.) area and compared responses of planners from similar‐sized jurisdictions that were “high” and “low performing” with respect to incorporation of biodiversity conservation in local planning. Planners from low‐performing jurisdictions regarded mandates from higher governmental levels as the primary drivers of biodiversity conservation, whereas those from high‐performing jurisdictions regarded community values as the main drivers, although they also indicated that mandates were important. Biodiversity conservation was associated with presence of local conservation flagship elements (e.g., salmonids) and human‐centered benefits of biodiversity conservation (e.g., quality of life). Planners from high‐ and low‐performing jurisdictions favored different planning mechanisms for biodiversity conservation, perhaps reflecting differences in funding and staffing. High performers reported more collaborations with other entities on biodiversity issues. Planners’ comments indicated that the term biodiversity may be problematic in the context of local planning. The action most planners recommended to increase biodiversity conservation in local planning was public education. These results suggest that to advance biodiversity conservation in local land‐use planning, conservation biologists should investigate and educate the public about local conservation flagships and human benefits of local biodiversity, work to raise ecological literacy and explain biodiversity more effectively to the public, and promote collaboration on biodiversity conservation among jurisdictions and inclusion of biodiversity specialists in planning departments.